AXIN1 bi-allelic variants disrupting the C-terminal DIX domain cause craniometadiaphyseal osteosclerosis with hip dysplasia - Terhal, Paulien; Venhuizen, Anton J.; Lessel, Davor; Tan, Wen-Hann; Alswaid, Abdulrahman; Grün, Regina; Alzaidan, Hamad I.; von Kroge, Simon; Ragab, Nada; Hempel, Maja; Kubisch, Christian; Novais, Eduardo; et al. (The American journal of human genetics, 2023)
Sclerosing skeletal dysplasias result from an imbalance between bone formation and resorption. We identified three homozygous, C-terminally truncating AXIN1 variants in seven individuals from four families affected by macrocephaly, cranial hyperostosis, and vertebral endplate sclerosis. Other frequent findings included hip dysplasia, heart malformations, variable developmental delay, and hematological anomalies. In line with AXIN1 being a central component of the β-catenin destruction complex, analyses of primary and genome-edited cells harboring the truncating variants revealed enhanced basal canonical Wnt pathway activity. All three AXIN1-truncating variants resulted in reduced protein levels and impaired AXIN1 polymerization mediated by its C-terminal DIX domain but partially retained Wnt-inhibitory function upon overexpression. Addition of a tankyrase inhibitor attenuated Wnt overactivity in the AXIN1-mutant model systems. Our data suggest that AXIN1 coordinates the action of osteoblasts and osteoclasts and that tankyrase inhibitors can attenuate the effects of AXIN1 hypomorphic variants.